Paralichthys isosceles - Riestra, C. (2020)
This demersal species occurs from southern Brazil to Argentina and is taken in multi-species commercial´s fisheries that target demersal fishes through much of its range. It is a relatively minor component of the catch of Paralichthys species as compared to catch of the sympatric P. patagonicus. For purposes of this assessment, half of the global population is considered to occur in Brazil and the other half in Uruguay and Argentina. According to landings and catch per unit effort data, the demersal fish stocks of Brazil are inferred to have declined by at least 30% and possibly to 50%. Due to the lack of specific data for this species, an estimate for population decline is not available or cannot be suspected at this time. According to stock assessment and fisheries data, there is no decline detected in the demersal stock in Argentina and Uruguay and abundance indices show an increase in recent years (since 2014). Fishing effort continues at an unsustainable level in Brazil, the fishery is not well-monitored and conservation measures are insufficient. Conservation measures in Argentina and Uruguay include a total allowable catch limit and regular monitoring of stock status. Based on the potential major threat from overfishing in at least half of its global population, but lack of quantified data, it is listed as Data Deficient with a recommendation to improve fisheries monitoring, including the collection of species-specific data, as" "well as implement conservation measures to reduce effort in Brazilian fisheries.